Career Adaptability Sebagai Variabel Prediktor Dalam Memprediksi Kesuksesan Karir Pada Fresh Graduate & Freelancer Akuntansi - Mawaddah, Tia; Handajani, Lilik; Suryantara, Adhitya Bayu (Akuisisi : Jurnal Akuntansi, 2024)
The term unemployment is closely related to the phrase minimal education, this is because college graduates cannot guarantee that they will easily get a job. A person's readiness in choosing a career is known as the concept of career adaptability. The real achievement felt by individuals accumulated from their work experience is called career success. The research method used is quantitative and the results of this research show that Career Adaptability has a significant positive effect on freelancers and fresh graduates in accounting. This can be seen from the indicators in the Career Adaptability variable, namely (Concern, Control, Curiosity and Confidence) and the Career Success indicators, namely (Job Level, Salary and Bonus, Contribution, Ability and Work-Life Balance) which are owned by freelancers and fresh graduate in accounting